Analisis dan Perancangan Ulang UI/UX SISKA UNSIKA Menggunakan Kuesioner Skala Likert - Najwa Latifah (Universitas Multi Data Palembang, 2026)
The Academic Information System (SISKA) of Singaperbangsa Karawang University (UNSIKA) is a platform used by students to manage various academic activities, such as course registration, viewing study results, class schedules, and other academic information. Although it has been widely used, there are still several issues that affect the quality of the user experience (UX) and user interface (UI). This study aims to evaluate the UI/UX of the SISKA UNSIKA website using a Likert scale questionnaire and provide redesign recommendations based on the results of user evaluation. The research method used is a descriptive quantitative approach with data collection through questionnaires distributed to 15 active UNSIKA students. The results show that the SISKA website obtained a satisfaction index score of 65.07%, which is categorized as good. The aspect with the highest score is the ease of understanding how to use the website, with 76.00%, while the aspects of color, icons, and layout received the lowest score at 57.33%. Based on the evaluation results, redesigns were made on several main pages, such as the dashboard, study plan, class schedule, thesis, and study results pages. The redesign resulted in a more modern, structured, and user-friendly appearance, and was able to improve user comfort and efficiency in accessing academic services.